Characterisation and control of the biosolids storage environment: Implications for E. coli dynamics - Fane, Sarah Elizabeth; Nocker, Andreas; Vale, Peter C. J.; Rivas Casado, Monica; Cartmell, Elise; Harris, Jim A.; Bajón Fernández, Yadira; Tyrrel, Sean F. (Elsevier, 2020)
E. coli survival in biosolids storage may present a risk of non-compliance with guidelines designed to ensure a quality product safe for agricultural use. The storage environment may affect E. coli survival but presently, storage characteristics are not well profiled. Typically biosolids storage environments are not actively controlled or monitored to support increased product quality or improved microbial compliance. This two-phased study aimed to identify the environmental factors that control bacterial concentrations through a long term, controlled monitoring study (phase 1) and a field-scale demonstration trial modifying precursors to bacterial growth (phase 2). Digested and dewatered biosolids were stored in operational-scale stockpiles to elucidate factors controlling E. coli dynamics. E. coli concentrations, stockpile dry solids, temperature, redox and ambient weather data were monitored. Results from ANCOVA analysis showed statistically significant (p < 0.05) E. coli reductions across storage periods with greater die-off in summer months. Stockpile temperature had a statistically significant effect on E. coli survival. A 4.5 Log reduction was measured in summer (maximum temperature 31 °C). In the phase 2 modification trials, covered stockpiles were able to maintain a temperature >25 °C for a 28 day period and achieved a 3.7 Log E. coli reduction. In winter months E. coli suppression was limited with concentrations >6 Log10 CFU g−1 DS maintained. The ANCOVA analysis has identified the significant role that physical environmental factors, such as stockpile temperature, has on E. coli dynamics and the opportunities for control
Keywords: Temperature; Log reduction; Pathogens; E. coli; Sewage sludge; Biosolids